Cardiac biomarkers for screening and prognostication of cardiac dysfunction in critically ill patients - Oscar Cavefors; Freyr Einarsson; Jakob Holmqvist; Odd Bech‐Hanssen; Sven‐Erik Ricksten; Björn Redfors; Jonatan Oras (ESC Heart Failure)
Abstract Aims This study aimed to assess the use of high‐sensitivity troponin T (hsTNT) and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) in screening for cardiac dysfunction [left ventricular (LV) systolic or diastolic dysfunction or right ventricular (RV) dysfunction] in mixed intensive care unit (ICU) patients and establish whether these biomarkers are independently associated with an increased risk of death. Methods We performed a secondary analysis of a single‐centre prospective observational study in which consecutive ICU patients were examined with transthoracic echocardiography (TTE) and cardiac biomarkers. Patients with systolic or diastolic LV dysfunction, RV dysfunction or a combination of these were compared with patients with normal cardiac function. Sensitivity and specificity for different cut‐off levels were calculated using receiver operating characteristic curves. Regression models were used to evaluate the associations between cardiac biomarkers, sepsis, renal failure and mortality. Results A total of 276 patients were included. Most of the patients had cardiac dysfunction on TTE (64%). Combined cardiac dysfunction was most prevalent (71 patients, 26%), followed by isolated diastolic LV dysfunction (40 patients, 15%). Levels of hsTNT and NT‐proBNP were higher in all types of cardiac dysfunction versus patients with normal cardiac function. The area under the curve (AUC) for hsTNT to detect any cardiac dysfunction was 0.75. An optimal cut‐off at 30.5 ng/L rendered a positive predictive value (PPV) of 80% and a negative predictive value (NPV) of 58%. The AUC for NT‐proBNP to detect any cardiac dysfunction was 0.788. Using an optimal cut‐off at 1145 ng/L rendered a PPV of 86% and an NPV of 58%. Using a clinically relevant 90% sensitivity for detecting cardiac dysfunction put the cut‐offs at 14.1 ng/L for hsTNT and 247 ng/L for NT‐proBNP, resulting in a specificity of 48% and 46%, respectively. Levels of NT‐proBNP were associated with sepsis and renal failure (P < 0.001), while levels of hsTNT were associated with renal failure only (P < 0.001) after adjustment for cardiac dysfunction. Levels of biomarkers were associated with an increased risk of 90 day mortality after adjustments for age, Simplified Acute Physiology Score 3, cardiac dysfunction and factors independently associated with biomarker increase (sepsis and renal failure) (P = 0.048 for hsTNT and P < 0.006 for NT‐proBNP). Conclusion Cardiac biomarkers, hsTNT and NT‐proBNP, are strongly correlated to cardiac dysfunction in ICU patients and have a robust association with increased mortality. However, the relatively low NPV and the low specificity at relevant sensitivity levels of the biomarkers make them unsuitable for use in screening for cardiac dysfunction.